1.1 μm waveband tunable laser using emission-wavelength-controlled InAs quantum dots for swept-source optical coherence tomography applications. (26th February 2021) - Tsuji, Toshiya; Ozaki, Nobuhiko; Yamauchi, Sho; Onoue, Katsuya; Watanabe, Eiichiro; Ohsato, Hirotaka; Ikeda, Naoki; Sugimoto, Yoshimasa; Childs, David T. D.; Hogg, Richard A.
Abstract: In this study, an optical gain chip using emission-wavelength-controlled self-assembled InAs quantum dots (QDs) was developed for swept-source optical coherence tomography (SS-OCT) applications. The optical characterizations indicated that the QDs emission wavelength and optical gain spectra were controlled in the 1.1 μ m waveband by optimizing the QDs growth conditions. This waveband is useful for obtaining a large imaging depth of OCT because of an optimal balance between absorption and scattering in biological samples. In addition, continuous tunable lasing in the waveband was achieved by introducing the QD-based gain chip into a grating-coupled external cavity. This tunable laser was introduced into an SS-OCT setup, and the point spread function (PSF) was evaluated. The PSF position was observed to vary according to the optical path length differences. These results demonstrate the feasibility of the application of emission-wavelength-controlled QDs for SS-OCT.